Retrieving the Returns to Experience, Tenure, and Job Mobility from Work Histories - John T. Addison; Pedro Portugal; Pedro Raposo (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using a unique Portuguese linked employer-employee dataset, this paper offers an extension of the standard Mincerian model of wage determination by allowing for different returns to experience and tenure over the sequence of jobs that constitute a career. We also consider the possibility of distinct wage hikes each time workers change jobs, where such uplifts reflect the returns to job search investments over the life cycle and shape the curvature of the earnings profile. We further investigate how worker, firm, and job match heterogeneity influence the returns to mobility, experience, and tenure. The returns to job mobility are found to reflect sorting into better job matches. Moreover, the estimated returns to experience are upwardly biased because more productive workers tend to be more experienced.
Keywords: J31; J63; 330; returns to tenure; returns to experience; job mobility; high-dimensional fixed effects; job match fixed effect; job match quality effect